Pengaruh Literasi dan Inklusi Keuangan terhadap Kinerja UMKM Kuliner di Kota Yogyakarta - Yulita Un; Diana Airawaty (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Culinary MSMEs (MSMEs) make a significant contribution to the regional economy, but they still face various obstacles in financial management and access to formal financial services. These conditions can affect the performance and sustainability of MSME businesses. This study aims to analyze the influence of financial literacy and financial inclusion on the performance of culinary MSMEs in Yogyakarta City in the context of the development of digital financial services and increasingly competitive business competition. The study used a quantitative approach with a survey method of 90 culinary MSMEs selected using a random sampling technique. Data were obtained through questionnaires and analyzed using multiple linear regression with the help of SPSS version 25. The results showed that financial literacy and financial inclusion have a positive and significant effect on the performance of culinary MSMEs, with a significance value of 0.000 < 0.05 for each. These findings indicate that financial management skills and easy access to formal financial services can improve the performance, sustainability, and competitiveness of culinary MSMEs in Yogyakarta City.